Dampak Tata Kelola Perusahaan Terhadap Tax Avoidance: Studi Pada Perusahaan Sektor Industri yang terdaftar di Bursa Efek Indonesia - Zenab, Nuna Siti; Kurniawan, Aceng (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the impact of corporate governance on Tax Avoidance in Indonesian companies. Good Corporate Governance is believed to be able to minimize Tax Avoidance practices that are detrimental to the state and create a more transparent and accountable business climate. In this study, data were obtained from industrial sector companies listed on the Indonesia Stock Exchange (IDX) 2021-2023. The method used is regression analysis with a quantitative approach to test the relationship between various corporate governance variables, such as Independent Commissioners, Institutional Ownership, Audit Committees, and Audit Quality, with the level of Tax Avoidance carried out by companies. The results of the study indicate that there is a significant influence between the quality of corporate governance and Tax Avoidance. Companies with higher levels of transparency and better governance tend to have lower levels of Tax Avoidance. Conversely, companies with poor governance are more susceptible to Tax Avoidance practices. This study contributes to the understanding of how the implementation of good governance can reduce Tax Avoidance, as well as provide implications for tax policy and ethical business practices in Indonesia.